Comparison of noninvasive pulse transit time determined from Doppler aortic flow and multichannel bioimpedance plethysmography - Soukup, Ladislav; Hruskova, Jana; Jurak, Pavel; Halamek, Josef; Zavodna, Eva; Viscor, Ivo; Matejkova, Magdalena; Vondra, Vlastimil (Medical & biological engineering & computing, 2019)
The main goal of this study was to make a comparison of aortic flow timing obtained by PW Doppler in four aortic sections with timing of - dZ/dt max obtained by bioimpedance measurement in nine locations on the thorax and neck. This knowledge is essential for determination of which bioimpedance channel could be used as a proximal for evaluation of pulse wave velocity (PWV) from the beginning of the ascending aorta or another aortic section. Time intervals between the Doppler flow and bioimpedance information (- dZ/dt max) were compared. It was found that the channel located on the left part of the neck is the most suitable as a proximal bioimpedance channel which corresponds to the aortic arch. This match is obtained with regard to the value of the time difference as well as inter-subject stability. This channel can be used as a proximal for evaluation of pulse wave velocity from the aortic arch to the desired distal target place in the body when distance between measured parts is known. The data from 35 volunteers with adequate signal quality were analyzed. Graphical abstract ᅟ.
Keywords: časové faktory; Ultrasonography, Doppler; pletyzmografie impedanční; aorta; Pulse wave velocity (PWV); Adult; dospělí; Pulse Wave Analysis; Humans; analýza pulzové vlny; Doppler ultrasound; Aorta; lidé; Bioimpedance; Plethysmography, Impedance; Time Factors; Pulse transit time (PTT); ultrasonografie dopplerovská